Preferences for the use of skincare products in Gen Z women from the perspective of marketing communication - Ananda, Alifia Maulidya; Putri, Aurora Rizkina; Andriany, Dian (International Journal Labs, 2024)
This study aims to find out how the preferences of Gen Z female consumers in purchasing skincare products based on the marketing messages they receive. The data collection technique in this study is to conduct observations and conduct in-depth interviews with Gen Z women who are actively using the product skincare. The results of the study show that the cognative stage, namely product knowledge and brand awareness, plays a crucial role in strengthening consumers' understanding of the existence of skincare products and their benefits. The conative stage is the endpoint in the purchase decision-making process, where consumers have formed a positive belief in skincare products. Effective marketing communication, especially through social media and collaboration with influencers or other user reviews, has a significant impact on shaping consumer preferences and guiding their purchasing decisions. This study can help skincare companies to develop a more effective marketing strategy that is in line with the preferences and purchasing behaviors of today's young consumers.